Notion and Essence of Administrative Procedure - K. P. Genning (Сибирское юридическое обозрение, 2012)
The notion of administrative procedure and its essence are being analyzed in the article. The author determines the legal procedure of administrative regulations, their role in social relations adjustment and offers also the directions for improvement of the state authority bodies activity in the sphere of administrative procedures preparation.